Red Cell Indices In Beta Thalassaemia Trait In Adult - Rahman, Md Maruf Ur; Nayem, Mohammad; Ahmed, Mohammad Nesar Uddin; Ahmed, Afsana; Aktar, Farjana; Sultana, Nasima (Journal of Dhaka National Medical College & Hospital, 2014)
Hypochromic & microcytic blood picture is one of the commonest abnormalities that a clinician come across in Bangladesh. A vast majority of such cases have iron deficiency. In Bangladesh about 3% of total population with a hypochromic and microcytic blood picture is beta thalassaemia trait. In areas where thalassaemia is common, differentiation between iron deficiency anaemia and the carriers of beta thalassaemia trait becomes problem. The uncomplicated beta thalassaemia trait usually have normal iron stores. Though they have microcytic hypocromic blood picture but they are resistant to iron therapy. With the presumption of iron deficiency, supplementation of iron to that cases produce iron overload and may produce organ dysfunction. So it is very important to distinguish between these two entities. Apart from estimation of Hb-A2, iron deficiency and beta thalassaemia trait can be differentiated on the basis of red cell count and red cell indices like MCV, MCH & MCHC. In this study 50 confirmed cases of beta thalassaemia trait aged 18 to 60 years of both male & female were included as cases & 50 cases of age & sex matched iron deficiency subjects were included as controls. RBC count, MCV, MCH & MCHC were measured by an electronic cell counter device. The present study revealed that RBC counts were higher in beta thalassaemia trait than in iron deficiency subjects and MCV, MCH & MCHC were significantly lower in iron deficiency subjects than in beta thalassaemia trait. J.Dhaka National Med. Coll. Hos. 2014;20(01):21-24